Stand age and species traits alter the effects of understory removal on litter decomposition and nutrient dynamics in subtropical Eucalyptus plantations - Yuanqi Chen; Yanju Zhang; Jianbo Cao; Shenglei Fu; Shuijin Hu; Jianping Wu; Jie Zhao; Zhanfeng Liu (Global Ecology and Conservation, 2019)
Litter decomposition is a crucial ecological process that regulates nutrient cycling. However, the effects of understory plants and overstory trees on litter decomposition and nutrient dynamics are still poorly understood. We conducted understory plants removal and/or overstory trees removal to examine the resulting effects on litter decomposition and nutrient mineralization in two Eucalyptus plantations with contrasting ages (8-yr-old, 29-yr-old) in subtropical China. Litter bags containing naturally senesced leaves of either overstory Eucalyptus urophylla or understory Dicranopteris dichotoma were placed in field and periodically collected for analyses of carbon (C), nitrogen (N), phosphorus (P) and calculation of mass loss. Our results showed that understory plants removal significantly reduced litter decomposition of E. urophylla in both plantations, but N and P mineralization were reduced only in the 8-yr-old plantation. In contrast, it reduced litter decomposition of D. dichotoma only in the 29-yr-old plantation, but had no effects on N and P mineralization in either plantation. In comparison, overstory tree removal did not have any effects on decomposition or mineralization of N and P of E. urophylla and D. dichotoma litters. These results indicate that the role of understory plants in mediating litter decomposition and nutrient mineralization is more important than overstory trees, and it can be altered by stand age and plant species. Our findings could facilitate the understanding of ecological processes of litter decomposition and nutrient mineralization in subtropical forest ecosystems. Keywords: Leaf litter, Understory plant, Nutrient mineralization, Subtropical forest, Stand age, Plant identity